Epistemology of Nationalism in the Context of National Jurisprudence at the Lirboyo Islamic Boarding School - Faizin, Khoirul; Mustamir, Ahmad Khoirul (IAIN Ponorogo, 2023)
This study discusses the epistemological reasoning of nationalism and national fiqh at Islamic boarding schools, especially at the Lirboyo Islamic Boarding School, Kediri, East Java. Lirboyo Islamic Boarding School was chosen purposively as the research location. With a case study approach, this article reveals the epistemological reasoning of nationalism that occurs and develops in the research location. The results of the study show that there has been a shift in the epistemology of nationalism. This epistemological shift can be seen from the inconsistency of meaning and choice of action taken. From the theory of social transformation, certain social constructions will also affect specific cognitions or awareness—likewise, the epistemology of nationalism at the Lirboyo Islamic Boarding School. During the phase of the struggle against Dutch colonialism, nationalism was interpreted as a form of jihad against non-Muslims, along with the emergence of an awareness of establishing an Islamic state. However, since the establishment of Ma'had Aly Lirboyo, which has the peculiarities of nationalism, nationalism has shifted in meaning to become a form of awareness against radicalism movements born of Islamic Group, such as Hizb at-Tahrir Indonesia (HTI) and the Islamic Defenders Front (FPI). The assertion that the State of Indonesia is a state whose government is legitimate and opposing it is a prohibited action further confirms this shift in the epistemology of nationalism.